Ameliorative effects of grape seed proanthocyanidins on cadmium induced metabolic alterations in rats - Bashir, Nazima; Manoharan, Vaihundam; prabu, Milton (International Journal of Biological Research, 2014)
Objective: To study the ameliorative effects of grape seed proanthocyanidins (GSP) against cadmium (Cd) induced hyperglycemia, hypercholesterolemia and hyperlipidemia in rats. Methods: Wistar rats, body weight 180-200g, were randomly divided into four groups, six rats in each group. First group (control) represented the control animal, the second group (Cd) was fed orally with Cd in the form of CdCl2 (5mg/kg bw), the third group (GSP) was fed with GSP (200 mg/kg bw) and to the fourth group (Cd+GSP), CdCl2 was administered orally at a dose of (5 mg/kg bw) and pre-treated with GSP (200 mg/kg bw) 90 min before Cd intoxication for 4 weeks. At the end of experiment, rats were sacrificed; blood and liver samples were collected and used for analysis of various metabolic parameters. Results: The result of the present study revealed that Cd exposure caused significant reduction in food intake and body weight gain, but increased the liver weight. GSP administration significantly revert all these changes to normal level. Cd intoxication induced hyperglycemia, elevate plasma glucose and lipid profiles and decline in high density lipoprotein (HDL) -cholesterol respectively. The GSP pre- treatment regimen was beneficial in the restoration of the increased serum levels of TC, TG and lipid profiles and of the suppressed insulin and total antioxidants on Cd exposure. Conclusion: From the present investigation, it may be concluded that Cd intoxication caused deleterious effects on the metabolism of rats which were successfully restored by GSP. Therefore, the present work suggests that GSP is a feasible therapeutic agent to improve and treat patients with hyperlipidemia, obesity, hyperglycemia in addition to its anti-oxidant properties and can be used as a component in food to promote the health of people.   Keywords: Cd, GSP, Carbohydrate Metabolism, Lipid Metabolism, Liver.